1961
DOI: 10.1113/jphysiol.1961.sp006791
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium in the secretory response of the adrenal medulla to acetylcholine

Abstract: It is commonly believed that acetylcholine (ACh) is the physiological transmitter of sympathetic nerve impulses at the adrenal medulla. The reasons are the following: the sympathetic nerve fibres that innervate the adrenal medullary cells are developmental homologues of the preganglionic fibres elsewhere in the sympathetic nervous system which are known to be cholinergic; on stimulation of the adrenal nerves an acetylcholine-like substance is released from the adrenal gland (Feldberg, Minz & Tsudzimura, 1934)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
358
1
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(380 citation statements)
references
References 26 publications
(34 reference statements)
20
358
1
1
Order By: Relevance
“…Since Douglas and Rubin [21] showed, in1961, that Ca 2+ entry was the only requirement to trigger the acetylcholinemediated release of catecholamines from the adrenal gland, we have learned much about basic and molecular aspects of Ca 2+ signalling and exocytosis in chromaffin cells. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Douglas and Rubin [21] showed, in1961, that Ca 2+ entry was the only requirement to trigger the acetylcholinemediated release of catecholamines from the adrenal gland, we have learned much about basic and molecular aspects of Ca 2+ signalling and exocytosis in chromaffin cells. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ca 2+ triggering of adrenaline secretion from chromaffin cells has been used as a general model for stimulus-secretion coupling [20]. According to the initial formulation, stimulus promotes Ca 2+ entry, which increases the cytosolic Ca 2+ concentration ([Ca 2+ ] C ) and triggers exocytosis [20,21]. Later studies showed that the genesis of the [Ca 2+ ] C signal includes subtle nuances contributed by the intracellular Ca 2+ -handling organelles [5,8,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In analogy with "electromechanical coupling" in muscle fibers for the chain of events between recognition of a stimulus and release of a secretory product, Douglas and Rubin [27] several years ago introduced the term "stimulus-secretion-coupling." In this process Ca z+ ions were believed to play an important role since Ca 2+ ions are required in the extracellular fluid to stimulate a secretory cell successfully [25,27,35,37,52].…”
Section: Discussionmentioning
confidence: 99%
“…In this process Ca z+ ions were believed to play an important role since Ca 2+ ions are required in the extracellular fluid to stimulate a secretory cell successfully [25,27,35,37,52]. Later from flux measurements in different systems it was concluded that an increase of intracellular Ca 2 + may be necessary for the transformation of the stimulus into release of secretory products [13,23,24,26,36,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal glands of the cats were retrogradely perfused at room temperature (25-28°C) through the adrenolumbar vein (DOUGLAS and RUBIN, 1961). Perfusion rate was kept constant (1 ml/min) by means of a peristaltic pump.…”
mentioning
confidence: 99%